Pruning Palms - Timothy K. Broschat (EDIS)
Perhaps the most fundamental question to answer when discussing palm pruning is what should a healthy, properly pruned palm look like? Consumers must be educated that palms are supposed to have round crowns, not feather-duster crowns. Learn more with this 9-page fact sheet written by Timothy Broschat and published by the UF Department of Environmental Horticulture, April 2011.